Pendekatan pengajaran, gaya belajar dan jenis penilaian dalam mata pelajaran sains sukan di sekolah menengah - Julismah Jani,; Ong, Kuan Boon; Mohd Sani Madon,; Hishamuddin Ahmad,; Nur Haziyanti Mohamad Khalid,; Yusof Ahmad, (penerbit ukm, 2009)
The aim of this study is to identify teachers’ teaching approach, students’ learning style, and types of evaluation of Form 4 sport science subject in secondary schools. The study also meant to identify the relationship between students’ learning style with their achievement in sport science subject. Samples consist of 208 teachers who thought in sport science subject and 2729 of students who participate in the sport science subject at selected secondary schools. Instruments used in the study consist of questionnaires for teachers and students with reliability of α = .962 and α = .799 respectively. The results showed that teachers’ teaching approach based on teaching management strategy was at medium level while its teaching techniques and teachers’ content knowledge on sport science were at high level. This study also found that students acquired a high interest towards sport science subject but at of a medium level on perceptual learning style which involve visual, auditory, and kinaesthetic. The evaluation styles chosen for measuring students’ learning achievement was written test, practical test, oral test, semester examination, project, and performance evaluation. Students’ learning achievement of Form 4 sport science subject was 9.2% scored grade A, 21% grade B, 38% grade C, and 18.5% grade D. Learning factor has a low significant relationship (r = .17**, p < .00) with students’ achievement in form 4 sport science subject. In conclusion, teachers’ teaching approach should anticipate with students’ learning styles and include varieties of evaluation process to evaluate students’ learning achievement in sport science subject.